The success of basketball teams in the enviroment of standard indicators of situational efficiency on three different levels of competition - Užicanin, E.; Babajic, F.; Kovacevic, E. (Sport Scientific and Practical Aspects - International Scientific Journal of Kinesiology, 2020)
This paper included research on the performance of basketball teams, which compete at three different levels of competition, the ABA , the ABA 2, and the BiH Championship. The research was conducted on a sample of 35 teams that played the BiH Championship (11 teams), ABA 2 (12 teams), and ABA (12 teams) in the 2018/2019 season. A total of 64 matches were played (20 matches of the BiH Championship, 22 matches of the ABA 2 , and 22 matches of the ABA ). Matches were analyzed using a standard form (FIBA) to monitor situation indicators with 22 variables, of which 19 were used in this paper. The main goal of this research was to find out whether it is possible to distinguish successful from unsuccessful teams at three different levels of competition based on 19 standard indicators of situational efficiency in basketball. Based on the results obtained by applied statistical methods, ie analysis of variance, the obtained information can be used as a starting point for analyzing the basketball game of one's team and determining future criteria for selection and programming of basketball teams. The obtained results showed that there are statistically significant differences between the winners at all three levels of competition in those statistical parameters that have a defensive character. So success, to a large extent depends on the realization of the phase of the game in transition, which can be the product of good defense and a jump in defense.